Program Indonesia Pintar: Masalah penyaluran KIP di Indonesia - Septiani, Ariani Candra Dwi (Maliki Interdisciplinary Journal, 2024)
The Smart Indonesia Program (PIP) is assistance issued by the government with the aim of distributing funds in cash as support for education to vulnerable primary to secondary school level students aged 6-12 years with economically disadvantaged family backgrounds. Recipients of this assistance program receive a Smart Indonesia Card (KIP) as a sign of PIP recipients. Even though it has great potential to improve education in Indonesia, the implementation of KIP often experiences obstacles and challenges. The aim of this research is to identify problems in the implementation of PIP throughout Indonesia using the literature study method. The research results show that the obstacles and challenges that often occur in the implementation of PIP are the lack of data accuracy and unclear targets for KIP recipients.